Cellulose nanofibril‐reinforced polypropylene composites for material extrusion: Rheological properties. Issue 5 (3rd May 2017) - Wang, Lu; Gardner, Douglas J.; Bousfield, Douglas W.
Abstract : Polypropylene (PP) is not typically utilized in 3D printing material extrusion because PP shrinks and warps during the printing process. Cellulose nanofibrils (CNF) have the potential to make PP 3D printer processable and also enhance mechanical properties of PP printed parts. The rheological behavior of CNF‐PP composites during material extrusion requires study because it is different from injection molding and compression molding processes. This study revealed the effects of CNF contents (3 and 10 wt%) and maleic anhydride polypropylene (MAPP) coupling agent on the rheological properties of CNF–PP composites. Morphological analysis showed that CNF agglomerated during spray drying and a spherical structure was formed. Rheological tests showed that the elastic modulus, complex viscosity, viscosity, and transient flow shear stress of PP were increased by the addition of 10 wt% CNF, while the creep strain of PP was reduced. The damping factor and stress relaxation time remained the same when 10 wt% CNF was added to the PP. Incorporation of MAPP into the CNF–PP composites impacted the rheological properties of the CNF–PP composites. Flexural strength and modulus of PP were improved by 5.9% and 26.8% by adding 10 wt% CNF compared to the control. POLYM. ENG. SCI., 2017. © 2017 Society of Plastics Engineers